Kinetic and chemical analyses of the biologic significance of lipoteichoic acids in mediating adherence of serotype III group B streptococci. - Nealon, T J (1985)
The mechanism(s) involved in the binding of lipoteichoic acid (LTA), isolated from virulent, asymptomatic, or avirulent serotype III strains of group B streptococci, to human embryonic epithelial cells (HEC), human fetal epithelial cells (HFC), and human adult buccal epithelial cells was investigated. It was determined that the binding of purified [3H]LTA to human adult buccal epithelial cells differed from the binding to HEC and HFC. LTA from all group B streptococcus strains bound to human adult buccal epithelial cells in a similar manner and was enhanced by the lipid portion of the polymer; in contrast, [3H]LTA binding to HEC and HFC was mediated by hydrophobic as well as specific interactions due to the glycerolphosphate backbone of LTA. Binding avidity of the LTAs to HEC and HFC varied depending on the bacterial strain. Polymers from asymptomatic and avirulent strains were easily dissociated from cell surfaces with unlabeled virulent LTA through competitive interactions; however, 10-fold greater levels of the same material were required to displace virulent [3H]LTA from HEC and HFC surfaces. These observed differences in binding avidity were shown to be due to longer LTA chains (30 to 35 glycerolphosphate units) in virulent strains when compared with LTA chains (10 to 12 glycerolphosphate units) of asymptomatic and avirulent strains. Thus, LTA appears to enhance the ability of virulent group B streptococci to bind to HEC and HFC with stronger avidity by virtue of the increased length of the cell-associated polymers synthesized by these strains. Mild enzymatic treatment of HEC and HFC with trypsin or periodate abolished LTA binding, which suggests the presence of a certain glycoprotein receptor(s) for LTA which does not appear to be present on human adult buccal epithelial cells. These data may therefore partially explain the increased susceptibility of newborn infants to group B streptococcal infections.